A Bibliometric Analysis of Scientific Publications at Universiti Malaysia Sabah - Krishnan, Anath Rau; Hamid, Rizal; Tanakinjal, Geoffrey Harvey; Bahri, Saiful; Arumugam, Nalini (Journal of Applied Science, Engineering, Technology, and Education, 2025)
This study presents a comprehensive bibliometric analysis of scientific publications associated with Universiti Malaysia Sabah (UMS) from 1994 to 2024, tracing the university’s research progression over three decades. Using data extracted from the Scopus database, the study analyzes 9,217 publications by document type, open access (OA) status, and author keywords across three distinct decades using tools like Power Query, Microsoft Excel 365, and VOSviewer version 1.6.20. Findings reveal a steady increase in scientific publication productivity, with journal articles dominating output and OA publishing experiencing a significant surge in recent years. The keyword analysis reveals a consistent emphasis on local issues, particularly those related to Sabah and oil palm, and also reflects the university’s increasing engagement with emerging global themes such as COVID-19, machine learning, and deep learning. This study offers the first comprehensive, cross-disciplinary bibliometric analysis of UMS publications, uniquely highlighting the university’s growing engagement with open access publishing. The findings offer valuable guidance for future policy decisions, particularly in enhancing publication funding, promoting balanced growth across disciplines, and advancing open science initiatives.